Digital video watermarking using discrete wavelet transform and singular value decomposition technique - P, Surekha; K N, Namratha; B Maigur, Vijaylaxmi (International Journal of Engineering and Technology, 2019)
The method of inserting data in the form of image, audio or video into a multimedia entity and then later identifying or extracting the inserted data is called watermarking. A basic example of digital watermark would be a visible identification positioned over an image to recognize the copyright. Based on the purpose of the watermark, it is inserted either perceptibly or imperceptibly. Digital Video Watermarking is developed to reduce the increasing illicit distribution of copyrighted video content. In this paper, Discrete Wavelet Transform (DWT) and Discrete Wavelet Transform (DWT) combined with Singular Value Decomposition (SVD) have been used to insert a watermark into all the frames of a video. The watermarked content is subjected to various attacks and their Normalized Correlation Coefficient (NCC) and Peak Signal to Noise Ratio (PSNR) are computed. The proposed technique has been found to be robust and imperceptible against attacks.Â Â